2016
DOI: 10.1016/j.ygyno.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

High expression of orphan nuclear receptor NR4A1 in a subset of ovarian tumors with worse outcome

Abstract: Objective Nuclear receptors (NRs) play a vital role in the development and progression of several cancers including breast and prostate. Using TCGA data, we sought to identify critical nuclear receptors in high grade serous ovarian cancers (HGSOC) and to confirm these findings using in vitro approaches. Methods In silico analysis of TCGA data was performed to identify relevant NRs in HGSOC. Ovarian cancer cell lines were screened for NR expression and functional studies were performed to determine the signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Overexpression of CYR61 has been shown to be associated with development and poor prognosis of ovarian carcinomas 46 . NT5E-expressing cancers were reported to be resistant to platinum-based therapy 47 , while NR42A has been reported to be highly expressed in ovarian cancer tumors with poor prognosis 48 . We found that these HIF1α-regulated genes play significant roles in ovarian cancer first-line chemotherapy resistance, leading to disease progression and poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CYR61 has been shown to be associated with development and poor prognosis of ovarian carcinomas 46 . NT5E-expressing cancers were reported to be resistant to platinum-based therapy 47 , while NR42A has been reported to be highly expressed in ovarian cancer tumors with poor prognosis 48 . We found that these HIF1α-regulated genes play significant roles in ovarian cancer first-line chemotherapy resistance, leading to disease progression and poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one report demonstrated that Nur77 is involved in the migration of transforming growth factor-β-induced breast cancer cells ( 32 ); furthermore, this process is dependent on p38α ( 33 ). Delgado et al ( 34 ) reported that the expression of Nur77 in ovaries was high relative to that in other tissues, with only skeletal muscle and tracheal tissue having higher levels of expression than the ovaries. In normal ovarian tissues, Nur77 is predominantly localized in the nucleus, whereas in ovarian cancer cell lines and tissues from patients with ovarian cancer, Nur77 is present in the cytoplasm and the nucleus.…”
Section: Structure Expression and Localization Of Nur77mentioning
confidence: 99%
“…In normal ovarian tissues, Nur77 is predominantly localized in the nucleus, whereas in ovarian cancer cell lines and tissues from patients with ovarian cancer, Nur77 is present in the cytoplasm and the nucleus. In addition, Nur77 was shown to be expressed at high levels in samples from a subset of patients with high-grade serous ovarian cancer, who had a poor progression-free survival rate ( 34 ), suggesting that Nur77 mediates the growth of cancer cells. Furthermore, Zhang et al ( 35 ) demonstrated that the expression of Nur77 was markedly reduced in the placenta of women with preeclampsia compared with placental levels during a normal pregnancy, and that Nur77 may also be involved in regulating trophoblast cell motility.…”
Section: Structure Expression and Localization Of Nur77mentioning
confidence: 99%
“…These receptors are early immediate genes induced by multiple stimuli and there is increasing evidence that NR4A receptors are potential drug targets for many diseases including cancer (47). Among the NR4A receptors, there has been extensive research on the expression and role of NR4A1 in cancer and one study found the loss of both NR4A1 and NR4A2 in mice results in hematological malignancies (8), suggesting tumor suppressor-like activity for NR4A1. In contrast, NR4A1 exhibits tumor promoter activity (6,7) in solid tumors.…”
Section: Introductionmentioning
confidence: 99%